TREN PENELITIAN TENTANG PENDIDIKAN ANTI KORUPSI DI PERGURUAN TINGGI DALAM PERSPEKTIF ANALISIS BIBLIOMETRIK - Definitif Endrina Kartini Medrofa; Ratna Indriasari; Cut Laila Karmila; Hestiwati Basir; Catur Widiatmoko; Gede Wijaya Kusuma (Kajian Ilmu Kepolisian dan Anti Korupsi Universitas Bhayangkara Jakarta Raya, 2025)
This study examines publication trends on anti-corruption education in Indonesian universities using a bibliometric approach. Secondary data was obtained from scientific journals published between 2019-2024 and analyzed through software to extract metadata, manage references, and visualize conceptual links. The analysis has revealed a significant increase with a total of 989 publications and 9,167 citations, resulting in an average of 9.27 citations per publication. The academic impact index showed an h-index of 44 and a g-index of 75. The network visualization identified 6 main thematic clusters reflecting the shift from conceptual studies towards evaluating the actual implementation of anti-corruption education programs. The findings emphasize the strategic role of universities in building an academic culture of integrity and provide a basis for developing more effective anti-corruption education strategies and policies in the future.